2018
DOI: 10.1097/sla.0000000000002297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgeon Age on Bariatric Surgery Outcomes

Abstract: When evaluating bariatric surgeons in the State of Michigan, we found no statistically significant association between surgeon age and patient outcomes. Our findings do not provide evidence for age-specific retirement cut-offs, but support the development of guidelines which are holistic, and focus on evaluating and improving physician outcomes at all career levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Los CJ que llevaron a cabo las intervenciones en nuestro estudio fueron formados durante el programa de residencia específicamente en CB, con un rotatorio en un centro internacional de alto volumen, y realizando las primeras intervenciones con la correcta supervisión de un CS. No obstante, el número de casos necesarios para cada procedimiento está vinculado a varios factores que a veces son difíciles de cuantificar, como las habilidades personales, la experiencia global del cirujano, la formación adecuada, el volumen de casos del hospital y la disponibilidad del equipo multidisciplinario 1,3,4 . Nuestros resultados son comparables a los de otros estudios publicados que afirman que la GVL realizada por CJ debidamente formados en centros de alto volumen, es igual de eficaz, segura y con similares resultados a corto y largo plazo que cuando es realizada por cirujanos más experimentados 5 .…”
Section: Discussionunclassified
“…Los CJ que llevaron a cabo las intervenciones en nuestro estudio fueron formados durante el programa de residencia específicamente en CB, con un rotatorio en un centro internacional de alto volumen, y realizando las primeras intervenciones con la correcta supervisión de un CS. No obstante, el número de casos necesarios para cada procedimiento está vinculado a varios factores que a veces son difíciles de cuantificar, como las habilidades personales, la experiencia global del cirujano, la formación adecuada, el volumen de casos del hospital y la disponibilidad del equipo multidisciplinario 1,3,4 . Nuestros resultados son comparables a los de otros estudios publicados que afirman que la GVL realizada por CJ debidamente formados en centros de alto volumen, es igual de eficaz, segura y con similares resultados a corto y largo plazo que cuando es realizada por cirujanos más experimentados 5 .…”
Section: Discussionunclassified
“…Although a few previous studies investigated obesity surgery and the age of the surgeon, these were mainly concerning the choice of surgery and postoperative complications [9]. In one study by Satkunasivam et al [10], higher surgeon age was associated with lower rate of postoperative complications and mortality, which was explained by the selection of patients with a lower risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…2 Some studies have found better outcomes with an increasing number of years of experience while other studies have described worse outcomes among oldest providers. [3][4][5][6] For example, obstetricians with more years of experience had fewer maternal complications. 3 On the other hand, very senior surgeons had higher morbidity and mortality in congenital heart surgery.…”
Section: Introductionmentioning
confidence: 99%
“…4 There was no statistically significant association between surgeon age and patient outcome in bariatric surgery. 5 One of the reasons outcomes suffer is surgeons’ technical inefficiency. Healthcare managers also concern about surgeon experience from the viewpoint of surgeons’ technical efficiency because they should know how efficiently surgeons can utilize healthcare resources.…”
Section: Introductionmentioning
confidence: 99%